Causes of Fall Hazards in Construction Site Management - Liy, Chong Hui; Ibrahim, Siti Halipah; Affandi, Rohaida; Rosli, Nor Azalina; Nawi, Mohd Nasrun Mohd (International Review of Management and Marketing, 2017)
Statistics from Occupational Safety and Health Act 1994 has shown that the number of fatality in the construction industry is 5 times more than in other sectors. The total fatalities in construction are 796 in year 2013 and out of this 796, there were 294 fall fatalities. Hence, there is an urgent need to mitigate this problem. A study has been conducted to investigate the root causes of fall hazards in construction site. Therefore, this paper is intended to identify and highlights the types of fall hazards that are most commonly found at construction sites today and the most causes contribute to fall as well as the most effective solutions to overcome the fall hazards. The data collection was being carried out through questionnaire survey to the construction company within Kuching areas. The data were then analyzed by using Likert scaling method. The finding of this study indicates that most fall hazards are caused by roof falls and scaffolding falls where communication barrier is the main problem causes the fall hazards. Besides, the responses from the survey had shown that workplace inspection that conducted weekly and through checklist and by informing affected workers involved about the result of the checklist is the adoptable typical measure to reduce the fall hazards. In conclusion, the problem of fall hazards could be improved and the findings of this study will be helped for further research as well as relevant reference in order to mitigate fall accidents in Kuching. Keywords: Fall hazard, site working condition, communication barrier, management commitment JEL Classification: C5